Endometrial injection of embryo culture supernatant adversely affects assisted reproductive technology outcomes in frozen thawed embryo transfer cycles - Ayumu Ito; Yukiko Katagiri; Kentaro Nakaoka; Mami Unagami; Koichiro Ichizawa; Kenji Amano; Yukiko Tokuda; Satoko Oigawa; Masato Yoneyama; Takahiro Tsuchiya; Mami Sekiguchi; Mayuko Furui; et al. (Scientific Reports)
Abstract We assessed the effects of endometrial injection of embryo culture supernatants on assisted reproductive technology (ART) outcomes in frozen-thawed embryo transfer (FET) cycles. Hormone replacement therapy cycles with blastocyst transfer on day 5 after fertilization were included, excluding cycles potentially affecting implantation. The stimulation of endometrial embryo transfer (SEET) group (118 cycles) received endometrial injections of the embryo culture supernatant, while the blastocyst transfer (BT) group (878 cycles) did not. Maternal age was significantly higher in the SEET than in the BT group (p < 0.05). The implantation, ongoing pregnancy, and live birth rates were significantly lower (all p < 0.05) in the SEET than in the BT group. Clinical pregnancy and miscarriage rates were not significantly different between the groups. Age-adjusted odds ratios (ORs) (95% confidence interval [CI]) for implantation and miscarriage were 1.02(0.69–1.52) and 1.97 (1.04–3.72), respectively, in the SEET group. Multivariate analysis was performed, including female age, BMI, AMH, and other potential factors influencing ART outcomes. The adjusted odds ratios (95% CI) for clinical pregnancy and miscarriage in the SEET group were 1.00 (0.63–1.58) and 2.08 (1.02–4.24), respectively. Additionally, the adjusted odds ratio for miscarriage was 0.732 (0.22–2.47) in patients aged < 37 years and 4.63 (1.61–13.3) in those aged ≥ 37 years. In conclusion, endometrial injection of the embryo culture supernatant may adversely affect ART outcomes in FET cycles, especially in maternal age ≥ 37 years.